Enhancing the Learning and Retention of Biblical Languages for Adult Students - Morse, MaryKate (Teaching theology and religion, 2004)
Finding ways to reduce students’ anxiety and maximize the value of learning Greek and Hebrew is a continual challenge for biblical language teachers. Some language teachers use technology tools such as web sites or CDs with audio lessons to improve the experience. Though these tools are helpful, this paper explores the value gained from understanding first how students learn and then how technology tools best support that learning. Developments in cognitive psychology and neuroscience offer many insights concerning adult learning and retention. After a presentation of key insights, several ideas are suggested for enhancing the learning and retention experience of biblical language students.